Flexible Nanocomposite Conductors for Electromagnetic Interference Shielding - Nan, Ze; Wei, Wei; Lin, Zhenhua; Chang, Jingjing; Hao, Yue (Nano-Micro Letters, 2023)
With the extensive use of electronic communication technology in integrated circuit systems and wearable devices, electromagnetic interference (EMI) has increased dramatically. The shortcomings of conventional rigid EMI shielding materials include high brittleness, poor comfort, and unsuitability for conforming and deformable applications. Hitherto, flexible (particularly elastic) nanocomposites have attracted enormous interest due to their excellent deformability. However, the current flexible shielding nanocomposites present low mechanical stability and resilience, relatively poor EMI shielding performance, and limited multifunctionality. Herein, the advances in low-dimensional EMI shielding nanomaterials-based elastomers are outlined and a selection of the most remarkable examples is discussed. And the corresponding modification strategies and deformability performance are summarized. Finally, expectations for this quickly increasing sector are discussed, as well as future challenges. Highlights: 1 Convincing candidates of flexible (stretchable/compressible) electromagnetic interference shielding nanocomposites are discussed in detail from the views of fabrication, mechanical elasticity and shielding performance. 2 Detailed summary of the relationship between deformation of materials and electromagnetic shielding performance. 3 The future directions and challenges in developing flexible (particularly elastic) shielding nanocomposites are highlighted.